Effecting between Emergency Department Overcrowding and Outcomes of nursing care: A Systematic Review at Saudi Arabia 2024 - Ahmed Nafea Dakhel Alhejaili, Bader Yahya Alnami, Aisha Hassan Omar Jupran, Ahmed Ali Ibrahim Hakami, Abdulmhosen Abdullah Allehyani, Ali Dhafer Saeed Al Bahish, Ali Faris Ali Al Gurayb (Journal of International Crisis and Risk Communication Research, 2025)
Background: Excessive overcrowding in emergency departments (ED) has become a global challenge, leading to decreased quality of healthcare services, especially in the nursing care, delayed patient treatment, and increased mortality rates. This issue is particularly pronounced in developing countries due to the inefficiency of healthcare systems and a lack of resources. Overcrowding in emergency departments (ED) is driven by several factors, including population growth, an aging demographic, inadequate hospital resources, the increasing complexity of patient needs, and operational challenges faced by healthcare providers and nursing . The emergency departments depend heavily on teams of interdisciplinary healthcare staff to carry out their operational goals and the core business of providing care to the seriously ill and injured. The ED is also recognized as a high-risk area concerning service demand and the potential for human error. Few studies have considered the perceptions and experiences of emergency department's staff (physicians, nurses, allied health professionals, and administration staff) regarding the practice of teamwork in nursing. The aim of this systematic review: To assess the effecting between emergency department Overcrowding and Outcomes of nursing care in Saudi Arabia 2024. Methods: This systematic review was conducted based on the Preferred Reporting Items for Systematic Reviews (PRISR) 2024 review protocol. We systematically reviewed the emergency department Overcrowding and Outcomes of nursing care. Results: Prolonged Overcrowding and Outcomes of nursing care and consultation time, and physical response to the final decision, and leads to burnout nurses and staff, wrong diagnoses, and management plans. Crowding issues are resolved by awareness, triad systems, and technological and telemedicine services .High patient expectations and overcrowding. Respondents emphasized the importance of education, security enhancements, and administrative support to address. Conclusion: ED crowding is becoming a major problem in the delivery of holistic care services in Saudi Arabia. High demand for emergency treatment should not be a hindrance to quality treatment. Physical, technological and strategic measures should be put in place to fight the crowding problem in the ED in Saudi Arabia, as it may cause adverse effects such as transmission of diseases and deaths of patients.